2010
DOI: 10.1002/star.200900253
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ethanol production for two corn varieties by commercial enzymes

Abstract: Two local corn hybrid varieties PMH‐1 and PMH‐2 were evaluated for ethanol production. Corn flour (2.0 mm) was prepared and liquefied with about 3 KNU/g of starch and saccharified subsequently with Spirizyme. Spirizyme concentrations were optimized as 5 and 7 AGU/g of starch for PMH‐1 and PMH‐2 with saccharification levels of 81.1 and 85.6%, respectively. The ethanol production was maximum at 20% solids with yields of 0.45 and 0.52 g/g of starch for PMH‐1 and PMH‐2, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Different maize varieties were oven dried at 65 °C to bring the moisture content of the grains at 8-12% for milling in a cemotec 1090 laboratory grinder mill and thereafter were sieved through a 2.0 mm sieve (Mangat et al 2010). Proximate analysis of all the three varieties of corn flour was done for estimating starch (Clegg 1956), crude protein, crude fibre, moisture content and ash content (AACC 2000).…”
Section: Proximate Analysis Of Maize Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different maize varieties were oven dried at 65 °C to bring the moisture content of the grains at 8-12% for milling in a cemotec 1090 laboratory grinder mill and thereafter were sieved through a 2.0 mm sieve (Mangat et al 2010). Proximate analysis of all the three varieties of corn flour was done for estimating starch (Clegg 1956), crude protein, crude fibre, moisture content and ash content (AACC 2000).…”
Section: Proximate Analysis Of Maize Varietiesmentioning
confidence: 99%
“…Moisture and ash content of three varieties have been found to vary between 11.08-12.02 and 1.37-1.63%, respectively. Mangat et al (2010) reported the composition of two maize varieties viz. PMH-1 and PMH-2.…”
Section: Proximate Analysis Of Maize Varietiesmentioning
confidence: 99%
“…Liquozyme SC and Spirizyme Fuel are two widely used enzymes in the corn ethanol industry to convert corn starch to glucose for fuel ethanol fermentation. Mangat et al (2010) reported that the maximal starch hydrolysis efficiencies were 81.1% and 85.6%, respectively, for two corn hybrids using the combination of these two enzymes. 35 Recently, Wang et al ( 2018) achieved a high starch hydrolysis efficiency of 94.5% after protein removal from corn.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mangat et al (2010) reported that the maximal starch hydrolysis efficiencies were 81.1% and 85.6%, respectively, for two corn hybrids using the combination of these two enzymes. 35 Recently, Wang et al ( 2018) achieved a high starch hydrolysis efficiency of 94.5% after protein removal from corn. 36 By a comparison with these two previous studies, we could conclude that the starch in food waste is as digestible as corn starch by commercial enzymes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%